Understanding the lac operon with GeneAct. (2015) - Yang, Xiaoli; Chen, Bin; Cai, Yifan; Tseng, Charles
GeneAct is a new framework developed to accelerate the coding of interactive programs for learning genetics. In this paper, the framework is used to create an interactive program for understanding the lac operon. Gene regulation, an inherent property of all organisms, is responsible for growth and development, as well as for an organism's ability to respond to changes in the environment. To illustrate the mechanisms of gene regulation, we highlight the operon system in bacteria because it is well defined and has widely been investigated. The control of the genes of the lac operon depends upon the availability of - and the nature of - the carbon source used for energy metabolism in bacteria. The interactive program based on GeneAct provides clearly defined tutorial tools for: 1) reading and thinking about the subject; 2) visualising the processes involved in regulating genes; 3) controlling the various molecular elements in the processes.